2014
DOI: 10.1063/1.4896250
|View full text |Cite
|
Sign up to set email alerts
|

Study of the electric field formation in a multi-cusped magnetic field

Abstract: The multi-cusped field thruster is a kind of electric thruster adopting a cusped magnetic field to achieve a potentially longer lifetime. It is observed in some experiments that the main electric potential drop forms near the exhaust plane, but the formation mechanism of the electric field in this kind of thrusters is not fully clear yet. Based on the analysis of the electron movement, a 2D Particle-in-Cell plus Monte Carlo model is built to reveal the difference of the constraint to electrons between the cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 12 publications
2
15
0
Order By: Relevance
“…The PIC mode also validated that the electrons concentrate at the region between the two separatrixes and near the middle separatrix [9]. However, at the main ionization region, the magnetic mirror effect and separatrix can resist the movement of the electrons.…”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…The PIC mode also validated that the electrons concentrate at the region between the two separatrixes and near the middle separatrix [9]. However, at the main ionization region, the magnetic mirror effect and separatrix can resist the movement of the electrons.…”
Section: Resultsmentioning
confidence: 76%
“…The Laser Induced Fluorescence (LIF) experiments [7] and the Particle-in-cell (PIC) simulations [8,9] showed that the electric potential drop is mainly formed at the exit of the discharge channel. The studies concerning the electric potential distribution and the low frequency oscillation have aroused great concern from different organizations.…”
Section: Introductionmentioning
confidence: 99%
“…The thruster has a great radial difference. A 2D Particle-in-Cell (PIC) simulation conducted by HIT Plasma Propulsion Lab (HPPL) has showed that the axial electron current density near the channel axis is much higher than that at other regions 7 . By other PIC simulations, the uneven radial distribution characteristic of the thruster has also been validated [8][9][10] .…”
Section: Iepc-2015-375/ists-2015-b-375mentioning
confidence: 99%
“…According to former researches on the cusped field thrusters, the electron confinement in the magnetic field is expected to be significant near the ultimate separatrix region (shown in figure 1), the electrons are strongly hindered and the main acceleration region is formed near the exit. 4,6 Therefore, it can be speculated that the small change of electron current I e and current utilization η c in different magnetic fields should be attributed to the well maintained magnetic field near the exit [in figure 4(c)].…”
Section: Aip Advances 6 095003 (2016)mentioning
confidence: 99%
“…The generated ions are accelerated by the mainly axial electric field near the exit and spurted out of the thruster, thus forming the thrust. 2 The laser-induced fluorescence (LIF) experiments [3][4][5] and Particle-in-Cell (PIC) simulations 6,7 have validated that the main acceleration region locates near the downstream of the thruster exit. Meanwhile, as the electrons are strongly confined by the mainly axial magnetic field in the discharge channel, the main ionization region can be established near the axis of the ultimate stage, as shown in figure 1.…”
Section: Introductionmentioning
confidence: 99%